Fiscal policy and the term structure of interest rates in a DSGE model - Ales Marsal; Lorant Kaszab; Roman Horvath (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
We examine the role of government spending in the dynamics of the term structure of interest rates. Is the quantity of risk related government spending important for the price of risk? How does it depend on monetary policy conduct? Can fiscal policy immunize its impact on the term structure of interest rates? To answer this questions, we explore asset pricing implications of fiscal policy in what become paradigm in dynamic general equilibrium macro-finance literature. We break down the transmission of the government spending to macroeconomic attributes driving the dynamic response of the yield curve, both analytically and numerically. The novelty of our approach lies in the way we quantify the decomposition of pricing kernel. We find that rise in fiscal uncertainty amplifies the hedging property of bonds against real and nominal risks. Depending on the size of uncertainty monetary policy drives up the price of nominal risk. Spending reversals break the link between quantity and price of fiscal risk.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: 330